Weeding of library collections in selected private high school libraries in Quezon City - Galang, Arnor T.; Faderon, Rosalie B. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1999)
The general purpose of this study is to determine the status of weeding of library collections in twenty-five selected private high school libraries in Quezon City. The survey method was used in the study. The study: 1)determined if weeding the library collection is an integral part of the collection management programs of private high school libraries in Quezon City; 2) determined if their written collection development policies include statements on the weeding of library collection; 3) identified their reasons in weeding out their library collections; 4) determined the methods and criteria in weeding; and 5) presented the problems encountered by these libraries in weeding library collections and came up with recommendations deemed useful for other high school libraries.
The findings reveal that: 1) all private high school libraries surveyed practice weeding of library collections; 2) majority (96 percent) of respondent librarians weed out library materials to get rid of unused or out-of-date materials; 3) more than half (52 percent) of the school libraries have no written weeding policies to guide the librarians in working with their library collections; 4) most (72 percent) of the school libraries store the weeded materials in a storage area/stock room in or near the same building while other libraries (28 percent) place the weeded materials in a storage area/stack room some distance away from the library; 5) majority of the respondent librarians used combined and/or multiple approaches to weeding; 6) dilapidated appearance (80 percent) and use patterns (80 percent) are the most frequently used criteria for weeding the book collection; 7) weeding the periodicals with very incomplete sets is the weeding criterion used considerably by most of the respondents for their periodical collections; and 8) weeding of library collections is not performed periodically in most of the private high school libraries because of the following problems: a) unavailability of storage area to house the weeded library materials; b) no systematic way of disposing weeded library materials; c) limited number of collection; d) can't replace old and dilapidated books which are in demand and useful because they are out-of-print; e) lack of manpower and time; f) faculty members are not cooperative with the librarian; g) there are more important things to be done; and h) it is hard to weed when there are several copies with different call numbers.
The study recommends the following: 1) weeding of library collections should be conducted on a regular basis in private high school libraries, for example, during summer breaks to have enough time and staff in weeding the library collection; 2) written weeding policies should be formulated in private high school libraries as well as in other school libraries; 3) librarians should encourage faculty members from each department to participate and cooperate actively in the weeding process; 4) lectures and seminars about weeding should be conducted; and 5) local standards and/or criteria for weeding library materials should be established.
Computer print out.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Collection development (Libraries) -- Philippines; Discarding of books,periodicals,etc; School libraries -- Philippines -- Quezon City